Management of tarsal tunnel syndrome: report of seven cases - Flavio A.P. Settanni; Lincoln M. Leandro; José A. Z. Zuleta; Eidmar A. Neri (Arquivos de Neuro-Psiquiatria, 1994)
Seven patients with clinical and electroneurographic evidence of tarsal tunnel syndrome were managed surgically, after failed attempts for non-surgical treatment. Post-operative results were more satisfactory than the previous responses to non-surgical therapies. Tarsal tunnel syndrome appears to respond better to surgical intervention than to conservative management.